Impact of the mobile terminal scheme on millimeter-wave radio over fiber systems based on photonic heterodyning techniques - Aldaya, Ivan [UNESP] (2017)
The use of communication networks relying on millimeter-wave (mm-wave) wireless links promises a great capacity enhancement as well as improved security. However, given the high-directivity of mm-wave links, coverage requirements are difficult to meet unless the network is assisted by an infrastructure. Given its low-cost, power-efficiency, and high capacity, radio over fiber has emerged as a strong candidate for the implementation of such infrastructure. Among the different generation techniques, photonic heterodyning has attracted considerable attention due to its capacity to generate radio frequency (RF) signals in the entire microwave/mm-wave range without requiring broadband electro-optical modulator. However, the RF signals generated using these techniques suffer from significant phase noise, a major impairment that degrades the system performance. In this paper we study two approaches to overcome this limitation: (1) the use of optical sideband injection locking (OSBIL) to generate tones with highly correlated phase noise and (2) heterodyning independent lasers in combination with a mobile terminal (MT) that is insensitive to the phase of the RF signal. A qualitative comparison between the two techniques in terms of MT sensitivity to the RF phase noise, the power sensitivity, and base station power efficiency leads to the conclusion that OSBIL is more suitable for networks with medium-range node separation, whereas heterodyning of independent laser with phase-insensitive MT is a cost-efficient solution for networks where nodes are closer to each other.